Synthesis and application of iron nanoparticles from scrap metal for triclosan degradation in water via Fenton and Sono-Fenton oxidation - S. Bhaskar; K.V. Apoorva; Shabina Ashraf; T. Athul Devan (Waste Management Bulletin)
Triclosan, a widely used antimicrobial agent in water known for its adverse effects was treated with Fenton and Sono Fenton oxidation. This study investigates the extraction of iron from scrap metal utilising acid digestion techniques and explores the production of iron nanoparticles for use as catalysts in Fenton and Sono-Fenton oxidation processes to degrade. Iron nanoparticles (FeSNPs) were synthesised using Mangifera indica plant extracts and characterized using scanning electron microscopy, X-ray diffraction, and electron diffusion spectroscopic spectrophotometry. Fenton and Sono-Fenton oxidation experiments were conducted with varying ratios of H2O2 to FeSNPs, and the maximum removal of triclosan was 59 % and 73 % for Fenton and Sono-Fenton oxidation, respectively, with rate constants of 0.0067 min−1 and 0.0210 min−1. The oxidation–reduction potential and pH played crucial roles in the efficiency of the oxidation processes. The total iron leached from the nanoparticles was 74.0 mg/L and 186.7 mg/L for Fenton and Sono-Fenton oxidation, respectively. At pH 3, the most effective ratio for triclosan removal by conventional Fenton oxidation was 1:4, whereas for Sono-Fenton oxidation it was 1:5. Sono-Fenton oxidation enhanced the production of hydroxyl radicals, resulting in a 14 % higher removal efficiency and a shorter treatment time compared to classical Fenton oxidation. Catalyst reusability studies demonstrated that Sono-Fenton oxidation maintained higher efficiency levels throughout multiple reuse cycles compared to Fenton oxidation. The results indicate the potential of utilizing iron nanoparticles derived from scrap metal as effective catalysts for the degradation of triclosan in water treatment applications. To recommend the most efficient Fenton oxidation method at an industrial scale, the study should be extended to evaluate the potential of these nanoparticles in both photo-Fenton and dark Fenton oxidation processes.